De novo podocytopathy following moderna COVID-19 vaccine: A case report and racial disproportionality in adverse effect reports - Hong, Li-Yu; Lee, Chii-Hong; Chiu, I-Jen (Frontiers in Medicine, 2022)
We reported a case of de novo minimal change disease shortly after the second dose of Moderna COVID-19 vaccine. A 51-year-old Asian man was previously healthy and presented lower limb edema and foamy urine three days after the injection. Laboratory data revealed his serum creatinine was 0.65 mg/dl, serum albumin was 1.3 g/dl and urine protein to creatinine ratio was 15.3 grams. A kidney biopsy was performed, and minimal change disease is confirmed. The patient reached complete remission at the tenth week after starting treatment of prednisolone 1mg/kg/day. Ethnic difference may influence the adverse effect of drugs or vaccine. However, there is very limited data to address the ethnic diversity in disease prevalence, clinical presentation, and treatment outcome in the COVID-19 vaccine associated glomerulonephritis.